المنظومة القانونية والرقابية وأثرها في تحقيق حماية حملة الصكوك: تجربة ماليزية The Legal and Regulatory System and Their Impact on Achieving the Protection of Sukuk holders: The Malaysian Experience - Mikail, Said Adekunle (International Journal of Al-Turath In Islamic Wealth and Finance, 2021)
يعد من أساسيات انتظام الصناعة المالية الإسلامية خضوعها للعديد من الحماية القانونية والتنظيمية التي أثرت بشكل مباشر أو غير مباشر على تقدم أنشطة الصناعة التمويلية والاستثمارية. وقطاع سوق رأس المال الإسلامية وخاصة الصكوك من أكثرها تأثرًا بذلك. لكن تداول الصكوك على المستوى الدولي والمحلي قد تعرقله اختلافات المنظومة القانونية والمذاهب الفقهية الأمر الذي قد يؤدى إلى ضعف التيقّن وخلل القوانين الحاكمة. ولا شك أن الاستثمار في الصكوك يستلزم توفير الطمأنينة والثقة من المستثمرين على وفرة الحماية اللازمة من القانون والجهاز الرقابي ووحدة الإطار التنظيمي وملائته لطبيعة الصكوك. وفي هذا الإطار يأتي هذا البحث لدراسة المنظومة القانونية والرقابية المطبقة على الصكوك في ماليزيا وكيفية تحقيقها لحماية حملة الصكوك. تم استخدام المنهج الوصفي والتحليلي لدارسة وضع هذه المنظمومة والبيانات الوثيقة بالموضوع والمصادر مع تحليلها لاستنباط عناصر حماية حملة الصكوك. توصل البحث إلى أن أهم أغراض المنظومة القانونية والرقابية وهو يكمن في كسب ثقة المستثمرين وتوفير الطمأنينة والشفافية وترسيخ العدالة يحول دون ذلك اختلاف القوانين وازدواجية الأنظمة الرقابية. وأن تطوير الصناعة بحاجة ماسة إلى إيجاد وتحسين الإطار التنظيمي الخاص بها لحل تحديات أو تقليلها، وإتاحة الفرص التنافسية مع الصناعة المالية التقليدية بالتساوي. Abstract One of the basics of the regularity of the Islamic financial industry is that it is subject to many legal and regulatory protections that directly or indirectly affected the progress of its financing and investment activities. The Islamic capital market sector, especially Sukuk, is one of the most affected products. However, the tradability of Sukuk at the international and local levels may be hindered by differences in the legal system and jurisprudential schools of thought, which may lead to a lack of certainty and a defect in the applicable laws. There is no doubt that investing in Sukuk requires providing reassurance and confidence from investors on the abundance of the necessary protection from the law, the supervisory apparatus, the unity of the regulatory framework and its adequacy with the nature of Sukuk. In this context, this research comes to study the legal and supervisory system applied to Sukuk in Malaysia and how to it helps actualize Sukuk-holders’ protection. A descriptive and analytical approach were employed to study the status of this system and the relevant data and sources, along with its analysis, to derive the elements of protection for Sukuk holders.The research finds that the most important objectives of the legal and regulatory system lie in gaining the confidence of investors, providing reassurance, transparency, and consolidating justice, the difference in laws and the instability of regulatory systems are stumbling blocks to all that. It is noteworthy that the development of the Islamic finance industry is in urgent need to either have its own regulatory framework or to improve the existing ones to address challenges or reduce them. It should be given competitive opportunities with the conventional financial industry on an equal footing. Keywords: Legal and Regulatory framework, Sukuk, Sukukholders’ protection, Malaysian experience.